How can the discipline of business case definition ensure that IT infrastructure programmes are completed successfully and deliver business value? - Gajendra, Nischal Nelpate (2009)
“Experian is a global leader in providing information, analytical and marketing services to organisations and consumers to help manage the risk and reward of commercial and financial decisions”. Experian UK, partners with more than 100,000 clients across multiple industry sectors providing businesses with competitive advantage and delivering real value to customers by combining the power of information assets and expertise that is unmatched in the industry. Experian is the only UK Company to win “Business of the Year” award twice.